Lateral Canthopexy in Lower Blepharoplasty: A Review Literature - Balakrishnan Ramalingam (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Lower eyelid malposition is a known complication of lower (lid) blepharoplasty surgery.The prevention of this complication is easier than its treatment. Over the past 10 years lot of patients havehad lower blepharoplasties with a canthopexy procedure and in some cases a tarsal strip canthoplasty. Thecriterion for a lateral tarsal strip canthoplasty was a lid distraction distance greater than or equal to 10 mm.Lid distraction distance is the distance the eyelid can be pulled away from the globe after the initial skinincision has been made and measured with calipers. If the eyelid can be pulled away from the globe less than10 mm, then a canthopexy is performed, which occurred in 98% of cases. Patients had lateral canthopexiesregardless of age or preoperative assessment. Herein, we describe a simple method of canthopexy that canbe performed on most patients having a lower blepharoplasty, to not only achieve a cosmetically superiorresult but also to prevent eyelid malposition or ectropion.Conclusion: We have described a simple prophylactic canthopexy suturing technique that all surgeonsperforming lower blepharoplasty can do to prevent rounding or ectropion. Naturally, the more cases that aredone, the more accurate will be the eyelid position and adequacy of eyelid tension achieved. Lateral tarsalstrip canthoplasty is also used in more advanced cases of lid laxity.